Psychopathological Dimensions in Substance Abusers with and without HIV/AIDS and Healthy Matched Group - Sajjad Rezaei; Sonbol Taramian; Seyed Mousa Kafie (Addiction and Health, 2013)
Background: Inattention to symptoms of mental disorders and substance abuse in patients with HIV/AIDS and other at-risk groups, may lead to irreversible damages. The purpose of this study was to compare the psychopathological dimensions in substance abusers with and without HIV/AIDS and healthy matched groups. Methods: In a cross-sectional and analytical study, selected samples (by available, consecutive, and objective methods) were 43 HIV-positive substance abusers, 49 HIV negative substance abusers under methadone maintenance therapy (MMT) in the counseling clinic of Behavioral Diseases and Addiction Abandonment, and 45 ordinary individuals. All of them were evaluated by matched confounding variables via Symptom Checklist-90-Revised (SCL-90-R). Findings: Results indicated a significant difference between these groups in the Global Severity Index (GSI), Positive Symptom Distress Index (PSDI), and Positive Symptom Total (PST) (P < 0.001). Two by two the comparison of the three groups from psychopathological dimensions revealed that substance abusers with HIV/AIDS persistently suffer more mental problems in all dimensions compared with healthy individuals (P < 0.05). In addition, in comparison with HIV negative substance abusers, they also suffer more mental problems in other dimensions, including somatization, interpersonal sensitivity, depression, anxiety, phobia, and psychoticism (P < 0.05). Yet, the difference in paranoid ideation, hostility, and obsessive-compulsive cases was insignificant. Two by two, the comparison between healthy individuals and substance abusers without HIV/AIDS showed higher levels of depression and psychoticism in substance abusers (P < 0.05), but no difference in other dimensions. Conclusion: Comorbidity of substance abuse and HIV diagnosis intensify mental disorder symptoms. Moreover, lack of prevention and implementation of appropriate psychological and psychiatric interventions after substance abuse and HIV lead to extended establishment of mental disorder symptoms. Keywords: Substance abuse, HIV/AIDS, Psychopathology, SCL-90-R